IMPLEMENTASI KEBIJAKAN PENANGGULANGAN BAHAYA KEBAKARAN DI KOTA SEMARANG - Frisca Windia Harera; Zainal Hidayat (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The implementation of the policies of fire hazard countermeasures in Semarang city is one of the regulation made by the Government as prevention of Semarang area and tackling a fire hazar because of it is increasing and loss either materially or casualties inflicted. The role of Government in Fire Department of Semarang and the community is very important to resolve the issue. The regional government demanded ,Semarang was able to complete the problems related to prevention and tackling the fire which occurred in accordance by applaying the local policy number 2 Year 1994 about Countermeasures with fire rescue by seeing some aspects namely surveillance, security , the availability of facilities and infrastructure, as well as the suitability of the procedures. This research is a descriptive qualitative research with informants staff on duty fire department of Semarang and self-described community is prone to fire rescue. This research aims to analyze the process of implementation of the policy and the factors that inhibit. The theory used in this study is George Edward III, who said that the factors of restricting implementation are disposition or attitude, communication, resources, and bureaucratic structure. The results of the research show that in the implementation of policies for tackling the fire in Semarang was still hampered by weak supervision, lack of human resources, financial resources or facilities, lack of awareness, lack of socialization. So it can be concluded that the implementation of policies for tackling the fire rescue in Semarang city have not been running well and optimally.